Mobile Learning Media for Islamic History Studies: Evaluation and Shaping Futures - Hasanah, Ida Faridatul; Hadi, Fais Nurul; Hasanah, Uswatun (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2022)
This study aims to develop, determine the feasibility and attractiveness of learning in the form of learning media based on mobile learning on Bani Umayyah material as an alternative learning. The type of research used is research and development with the Borg and Gall model. Product feasibility is carried out by validating material experts and media experts. Then the researchers conducted a small group attractiveness test to 10 students and a field trial by 35 students to see the students' responses. This research produces a product in the form of an SKI learning application that contains material for the Bani Umayyah chapter 1. The results show that mobile learning-based learning media is feasible with a percentage achievement of 83.4% according to material experts and 85.2% according to media experts. The results of the trial on students showed a percentage of 85.6% with very interesting criteria. So it can be concluded that mobile learning-based learning media with decent quality and attractiveness can be effectively used as alternative learning media. Therefore, more rigorous studies on the development of mobile learning principles and frameworks in various contexts are necessary for future Islamic studies.